Teacher Learning and Professional Development: Views and Practices of Georgian and Turkish Teachers of English - Nino Mikeladze; Servet Celik; Tamar Dolidze (European Scientific Journal, ESJ, 2023)
By the time they graduate from their initial teacher education programs, most teachers are equipped with the basic information and skills they may need to begin their classroom practice – including content knowledge, theories about the teaching and learning process, and various instructional strategies and techniques. However, the process of becoming a teacher does not end there. The most successful teachers are also lifelong learners who continuously work to improve their subject-related knowledge, understand how they can reach their students most effectively, and keep up with new developments in education. Considering the need for teachers to be aware of the concept of teacher learning and their beliefs that impact their practice in that regard, this comparative study will explore and report initial findings of what Georgian and Turkish teachers of English understand from the concepts of “teachers as learners” and “teacher learning,” and what kinds of professional development activities and efforts they are involved in as part of what they think these concepts constitute and require.